Natural Antioxidant Activities of Plants in Preventing Cataractogenesis - Eva Imelda; Rinaldi Idroes; Khairan Khairan; Rodiah Rahmawaty Lubis; Abdul Hawil Abas; Ade John Nursalim; Mohamad Rafi; Trina Ekawati Tallei (MDPI AG, 2022)
A cataract is a condition that causes 17 million people to experience blindness and is the most significant cause of vision loss, around 47.9%. The formation of cataracts is linked to both the production of reactive oxygen species (ROS) and the reduction of endogenous antioxidants. ROS are highly reactive molecules produced by oxygen. Examples of ROS include peroxides, super-oxides, and hydroxyl radicals. ROS are produced in cellular responses to xenobiotics and bacterial invasion and during mitochondrial oxidative metabolism. Excessive ROS can trigger oxidative stress that initiates the progression of eye lens opacities. ROS and other free radicals are highly reactive molecules because their outer orbitals have one or more unpaired electrons and can be neutralized by electron-donating compounds, such as antioxidants. Examples of natural antioxidant compounds are vitamin C, vitamin E, and beta-carotene. Numerous studies have demonstrated that plants contain numerous antioxidant compounds that can be used as cataract preventatives or inhibitors. Natural antioxidant extracts for cataract therapy may be investigated further in light of these findings, which show that consuming a sufficient amount of antioxidant-rich plants is an excellent approach to cataract prevention. Several other natural compounds also prevent cataracts by inhibiting aldose reductase and preventing apoptosis of the eye lens.